General Split Variational Inclusion Problem in Hilbert Spaces - Li Yang; Fu Hai Zhao (Abstract and Applied Analysis)
We consider a general split variational inclusion problem (GSFVIP) and propose an algorithm for finding the solutions of GSFVIP in Hilbert space. We establish the strong convergence of the proposed algorithm to a solution of GSFVIP. Our results extend and improve the related results in the literature.